2013
DOI: 10.1007/s10509-012-1346-5
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and phantom scalar fields as an interaction of two perfect fluids

Abstract: In this article we investigate and develop specific aspects of Friedmann-Robertson-Walker (FRW) scalar field cosmologies related to the interpretation that canonical and phantom scalar field sources may be interpreted as cosmological configurations with a mixture of two interacting barotropic perfect fluids: a matter component ρ1(t) with a stiff equation of state (p1 = ρ1), and an "effective vacuum energy" ρ2(t) with a cosmological constant equation of state (p2 = −ρ2). An important characteristic of this alte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…A scalar field model of the universe with both stiff fluid and an effective interacting vacuum were proposed by Cataldo et al [11]. The authors have considered a scalar field in FLRW universe and shown that, the field can effectively manifest as a mixture two barotropic fluids, one with an equation of state p = ρ, corresponding to the stiff fluid and the other with an equation of state p = −ρ mimicking the vacuum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A scalar field model of the universe with both stiff fluid and an effective interacting vacuum were proposed by Cataldo et al [11]. The authors have considered a scalar field in FLRW universe and shown that, the field can effectively manifest as a mixture two barotropic fluids, one with an equation of state p = ρ, corresponding to the stiff fluid and the other with an equation of state p = −ρ mimicking the vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Let us consider the evolution of a self interacting scalar field, φ. which is minimally coupled to gravity in flat isotropic and homogeneous universe. In describing the evolution of the scalar field we mainly follow the reference [11], so for more details see that reference. The evolution of the scalar field is governed by the equations…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve this problem, many approaches emerged [5][6][7][8]. One interesting suggestion was a diffusive exchange of energy between dark energy and dark matter made by Calogero [9,10], Haba et al [11], and Szydlowski and Stachowski [12], with some solution to cosmic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the above physical motivations, many authors focused the attention on the mathematically rigorous treatment of cosmological models with scalar fields. Exact solutions of the Einstein equations for these models are obtained in [12,18,[22][23][24][25][26][27][28][29][30][31][32][33]. Again, in the area of exact solutions, we would mention a peculiar, "inverse" approach to the evolution equations of scalar cosmologies: here the time dependence of the scale factor (or of some other physically relevant quantity) is prescribed, and the Einstein equations are used to determine the other observables of the model, including the self-interaction potential of the scalar field [5,10,34,35].…”
Section: Introductionmentioning
confidence: 99%